Top Management Attention to Innovation: The Role of Search Selection and Intensity in New Product Introductions - Li, Qiang; Maggitti, Patrick G.; Smith, Ken G.; Tesluk, Paul E.; Katila, Riitta (Academy of Management Journal, 2013)
We develop and test an attention-based theory of search by top management teams and the influence on firm innovativeness. Using an in-depth field study of 61 publicly traded high-technology firms and their top executives, we find that the location selection and intensity of search independently and jointly influence new product introductions. We have three important findings. First, in contrast to the portrait of local managerial search, we find teams that select locations that contain novel, vivid, and salient information introduce more new products. Next, unlike information-gathering approaches that merely “satisfice,” persistent search intensity may lead to increases in new product introductions. Finally, level of search intensity must fit the selected location of search to maximize new product introductions.